Sunni Syiah: Titik Perbedaan dan Kemungkinan Harmonisasi antara Keduanya - Abdul Rahman; Indo Santalia; Tabhan Syamsu Rijal (Journal of Innovative and Creativity, 2025)
This study investigates the historical, theological, and socio-political differences between Sunni and Shia Islam. By examining core issues such as leadership, understanding of the Prophet's companions, and interpretation of the Quran, the study highlights the complex factors that contribute to sectarian divisions. The paper then explores the potential for harmonization between the two sects, focusing on the importance of interfaith dialogue, education, and community-building initiatives. Although Sunnis and Shias share a common foundation in Islamic belief, their differing perspectives on key doctrinal and historical issues have caused sectarian tensions for centuries. The study argues that by fostering mutual understanding, promoting tolerance, and addressing the underlying political and social factors, sectarian conflict can be reduced and bridges can be built between Sunni and Shia communities. The paper concludes by emphasizing the importance of continued dialogue and cooperation in achieving lasting peace and harmony in the Muslim world.